Test Platform Design of Integrated Controller for Electric Vehicle Based onUDS Protocol - XIONG Gang; WANG Wenming; XIE Yongbo; FENG Ba (Kongzhi Yu Xinxi Jishu, 2021)
In order to improve the efficiency and versatility of factory function test of electric drive integrated controller for electric vehicles, it constructs an automated universal test platform based on unified diagnostic services (UDS) protocol. A pure digital representation method of data identification (DID) is designed for detection model, and the collection of this model is used as the detection configuration file to achieve the universality of the detection platform. The detection items are decomposed and designed by category, and the DID is uniformly assigned. Combined the detection model, a diagnostic protocol is designed for tested products, which realizes flexible control and data reading of the detection for integrated controller, and reduces the link of writing detection program in traditional detection. Practical application results show that the test bench can meet the generalization requirements of integrated controller, simplify the test process compared with the traditional test bench, and improve test efficiency by nearly 31%.